Temperature dependence of electrical characteristics of Pt/GaN Schottky diode fabricated by UHV e-beam evaporation - Kumar, Ashish (Springer, 2013)
Temperature-dependent electrical characterization of Pt/n-GaN Schottky barrier diodes prepared by ultra high vacuum evaporation has been done. Analysis has been made to determine the origin of the anomalous temperature dependence of the Schottky barrier height, the ideality factor, and the Richardson constant calculated from the I-V-T characteristics. Variable-temperature Hall effect measurements have been carried out to understand charge transport at low temperature. The modified activation energy plot from the barrier inhomogeneity model has given the value of 32.2 A/(cm(2) K(2)) for the Richardson constant A** in the temperature range 200 to 380 K which is close to the known value of 26.4A/(cm(2) K(2)) for n-type GaN.